Using Student’s Examination Results in Evaluation of Curriculum Amendments at the Faculty of Medicine, University of Kordofan, Sudan - Awadalla, Khidir E; Mohammedelhassan, Yassir A.; Magzob, Mamoun; Hamad, B. (IJRDO- Journal of Educational Research, 2018)
Background: Educational evaluation data collection and analysis is used for judging about capabilities and shortage of an educational program. Methods: The results of milestone examinations of students before and after the amendment of the curriculum were compared to see if there is any statistically significant difference between the two groups using SSPS. Results: There is improvement in the performance of students who have studied with the modified curriculum in final examinations results in physiology and biochemistry (p value ≤ 0.01, both of them). Also in clinical subjects as Medicine, Obstetrics & Gynaecology and Paediatrics, the performance of students in final examinations was better than their performance in these subjects before amendments, and this was obvious in their results in these examinations, (p value ≤ 0.01 in all these subjects). Conclusion: In our opinion, modified curriculum is better than the old one (before amendments), though student’s examination results were the only available measure, but it may need more time and other assessment tools to be evaluated perfectly.